Plant defense : warding off attack by pathogens, herbivores and parasitic plants - Walters, Dale R. (Chichester, West Sussex, U. K. ; Ames, Iowa : Wiley-Blackwell, 2011)
Plant Defense provides comprehensive coverage of the range of different organisms that plants need to fend off, describes how plants coordinate their ddefenses against multiple attacks, explains the evolution of defense in plants, and how plant defences are exploited in crop protection strategies
Plants are sources of nourishment for thousands of fungi, bacteria, invertebrates, and other plants.Plants process a truly remarkable diversity of mechanisms to fend off attackers and recent research has shown just how complex and sopisticated these defense mechanisms can be
1. Why do plants need defenses? -- 2. What defences do plants use? -- 3. Sounding the alarm: signaling and communication in plant defense -- 4. Plant defense in the real world: multiple attackers and beneficial interactions -- 5. The evolution of plant defense -- 6. Exploiting plant defense
Includes bibliographical references and index
Keywords: Plants -- Disease and pest resistance